Kinetics and Mechanism of Oxidation of Aliphatic Alcohols by N-Bromonicotinamide in Aqueous Acetic Acid - MATHIYALAGAN*, N.; SHENBAGAM, K.; KAVITHA, M. (Asian Journal of Chemistry, 2009)
Kinetics of oxidation of four aliphatic alcohols by N-bromonicotinamide (NBN) in 60 % aqueous acetic acid has been investigated. The reaction follows first order kinetics with respect to both [NBN] and [Substrate]. A increase in the dielectric constant increases the rate. Addition of nicotinamide has a negligible effect on the rate of oxidation. The product of oxidation is the corresponding aldehyde and ketone. From the effect of temperature on the reaction rate the Arrhenius and activation parameters have been calculated. A suitable mechanism has been proposed and rate law explaining the experimental results is derived.